ANALISIS KESULITAN BELAJAR YANG DIHADAPI SISWA PADA PEMBELAJARAN GEOGRAFI DI MASA PANDEMI COVID-19 (Studi Kasus di MAN 2 Pontianak) - Nurul Ayu Annisa; Nuraini Asriati; Agus Sugiarto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to identify the factors causing learning difficulties in Geography instructions in class XI Social Sciences MAN 2 Pontianak during the Covid-19 pandemic. The method used in this study was a descriptive approach with qualitative research in the form of a case study. Research data sourced from Class XI Social Sciences Students and Geography Teacher. The data collection tools used were questionnaires and interviews. The results of this study indicate that there are internal and external factors that influence the learning process of Geography. Internal factors include lack of interest in learning, study habits, and students' physical condition. External factors include the state of the house situations, the lack of facilities for learning at home, the lack of parental attention to children, and the relationship between teachers and students. Efforts that students can do to overcome learning difficulties are finding other references through social media, asking questions and discussing with classmates, and organizing better and more effective time management. In addition, the effort that teachers can do is to foster students' motivation and interest in learning by providing more interesting learning materials such as learning videos.Keywords: Covid-19 Pandemic, E-Learning, Geography Instructions, Learning Difficulties.